2018
DOI: 10.5603/ep.2018.0059
|View full text |Cite
|
Sign up to set email alerts
|

Endokrynne implikacje otyłości i zabiegów bariatrycznych

Abstract: Obesity is a highly prevalent disease in the world associated with the disorders of endocrine system. Recently, it may be concluded that the only effective treatment of obesity remains bariatric surgery. The aim of the review was to compare the concepts of appetite hormonal regulation, reasons of obesity development and bariatric procedures published over the last decade. The reviewed publications had been chosen on the base on: 1. reasons and endocrine consequences of obesity; 2. development of surgery method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
(83 reference statements)
2
13
0
1
Order By: Relevance
“…Bariatric surgeries have a strong impact on the metabolism, carbohydrates, and lipid turnover as well as on the hormonal system [3,21,22].…”
Section: Figure 4 Blood Ghrelin Levels [Fmol/ml] In Females Before (mentioning
confidence: 99%
See 3 more Smart Citations
“…Bariatric surgeries have a strong impact on the metabolism, carbohydrates, and lipid turnover as well as on the hormonal system [3,21,22].…”
Section: Figure 4 Blood Ghrelin Levels [Fmol/ml] In Females Before (mentioning
confidence: 99%
“…Increased release of corticoliberin from the hypothalamus stimulated synthesis and release of the adrenocorticotrophin from proopiomelanocortin. Paradoxically, proopiomelanocortin (POMC), the anorexigenic regulator of food uptake, is the precursor of enkephalins, which stimulate food intake [3].…”
Section: Figure 4 Blood Ghrelin Levels [Fmol/ml] In Females Before (mentioning
confidence: 99%
See 2 more Smart Citations
“…Resistin is one of the best-known adipocytokines. Over the years its blood concentrations have been tested, and its role in the pathogenesis of obesity, arterial hypertension, cardiovascular diseases, and stroke has been studied [16,17]. Qian et al [18] showed a higher concentration of this adipocytokine in the blood of obese mice.…”
Section: Resistinmentioning
confidence: 99%